Design and realization of efficient & secure multi-homed systems based on random linear network coding - Noura, Hassan N.; Melki, Reem; Malli, Mohammad; Chehab, Ali (Computer networks (Amsterdam, Netherlands : 1999), 2019)
Multi-homing is a new mechanism that enables hosts with multiple network interfaces (IP addresses), to connect to more than one data link. This technology enhances Internet connectivity and reliability without compromising efficient performance. Like any communication system, the security of multi-homed systems is of great importance. However, this issue remains largely un-attempted, where only few papers in the literature discuss, address and present security solutions for multi-homed systems. On the other hand, Random Linear Network Coding (RLNC) has recently emerged as a new coding technique that aims at improving system performance by efficiently transmitting and compressing data in general multi-source multicast networks. In this paper, a data confidentiality and availability scheme based on RNLC, is proposed for multi-homed systems. The proposed solution exploits the random physical characteristics of wireless channels, along with a pre-shared secret key, to derive dynamic keys which are used to generate random and dynamic cryptographic primitives. These primitives mainly include two permutation tables and a set of secret invertible RLNC matrices, all of which change for every input message. It has been shown that by securing the cryptographic primitives needed in the ciphering/deciphering process, one can jointly enhance the security and performance of transmitted data in multi-homed systems. Finally, security and performance analysis are presented to validate the efficiency and security of the proposed encryption/encoding scheme.